Study protocol for a randomised controlled trial of cognitive processing therapy for post-traumatic stress disorder among Japanese patients: the Safety, Power, Intimacy, Esteem, Trust (SPINET) study. Issue 6 (30th June 2017) - Ito, Masaya; Horikoshi, Masaru; Resick, Patricia A; Katayanagi, Akiko; Miyamae, Mitsuhiro; Takagishi, Yuriko; Takebayashi, Yoshitake; Kanie, Ayako; Hirabayashi, Naotsugu; Furukawa, Toshiaki A
Abstract : Introduction: Cognitive processing therapy (CPT) is widely regarded as a safe and effective first-line treatment for individuals with post-traumatic stress disorder (PTSD); however, no comparative studies have been conducted to examine the treatment outcomes in an Asian population. The aim of the present trial is to investigate the efficacy of CPT (individual format) as a treatment for PTSD in a population of Japanese patients. Methods and analysis: A 16-week, single-centre, assessor-masked, randomised, parallel-group superiority trial has been designed to compare the efficacy of CPT in conjunction with treatment as usual (mostly pharmacotherapy and clinical monitoring) versus treatment as usual alone. The Clinician-Administered PTSD Scale for the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) will be our primary outcome measure of the post-traumatic stress symptoms at 17 weeks, whereas the PTSD Checklist for DSM-5 and determination of the operationally defined responder status will be used to assess the secondary outcomes. An estimated sample size of 29 participants in each group will be required to detect an expected effect size of 1.4 (95% CI 0.85 to 1.95). Ethics and dissemination: The institutional review board at the National Center of Neurology and Psychiatry in Japan approved this study. The results of this clinical trial will be presented at conferences and disseminated through publication in a peer-reviewed journal. Trial registration number: UMIN000021670 (registered on 1 April 2016).